Photogrammetry to maintain heirloom authenticity - Miftah Amirul Amin; Muhammad Emir Ghiffari; Muhammad Arham Irsyad; Umar Ali Ahmad; Reza Rendian Septiawan; Fussy Mentari Dirgantara; R Rogers Dwiputra Setiady (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
Heirlooms are very valuable items because they have a strong historical value. But in reality, many heirlooms are damaged as a result of the negligence of visitors who want to see the heirlooms or because of a disaster. Photogrammetry is a technology that is developing and is often used for today's industrial needs so that it offers an alternative solution for documenting heirlooms in the form of 3D models. This study aims to implement photogrammetry to document heirlooms. With the application of this technology, it is hoped that it can be used as a prevention or solution if heirlooms are damaged because we can make new duplicates of heirlooms based on 3D models that have been made. This research was conducted at Kanoman Palace, Cirebon City. The results of photogrammetry after it is implemented show that all needs are met and can be used as needed. The results of the questionnaire to the Kanoman Palace and people in Cirebon City, showed a figure of 73.7% strongly agree that the photogrammetry results are similar to the original heirlooms and strongly agree that by making 3D models of heirlooms can be used as prevention and solutions if the heirlooms are damaged.